Korean dance : Pure emotion and energy - File, Curtis (Korea essentials ;, 2013)
Dance has been a medium for understanding the philosophy of and emotions behind a culture. This is especially true for a country with a vast and complex history like Korea. Korean dance is a tradition that includes every form of contemporary dance in the country, from shamanistic to folk, court to modern traditional dance, and even breakdancing. Over the past several centuries, each of these unique dance forms has attempted to convey the Korean psyche. This book aims to examine Korean dance from its primitive roots to the complex court rituals and on to the pop culture styles of today.